Extraction and deproteination of extracted silk fibers from silk cocoon and development of hydrophilic electrospun silk fibers / Nurul Afiqah Mohd Zaki - Nurul Afiqah , Mohd Zaki (2016)
Silk fibroin protein derived from Bombyx Mori silk cocoon is a natural polymer that widely used for application in tissue engineering. Silk Fibroin has remarkable properties that demonstrates biocompatibility, biodegradable and great mechanical properties. In this present study, regenerated silk fibroin can be obtained by multistep preparation which are degumming and solubilisation process. The small pieces of regenerated silk fibers were cut and then blended with Polyvinylalcohol (PVA) solution to enhance the mechanical property of scaffold. Electrospinning capable to fabricate scaffold with the high surface area. Result showed that by increased of concentration of solution silk/PVA, voltage and flowrate, more fibers were produced in the film. A thin white film was produced at film of silk/PVA at 14% (w/v) without addition of chloroform. Scanning Electron Microscope (SEM) investigated the morphology of silk and revealed that applied voltage of 15kV during electrospinning has narrowest of fiber diameter (0.270 μm), less number of beaded, smaller beads and high average size of pore (1.379 μm). Flowrate parameter showed that more electrospun fibers were produced at 3 ml/h with fiber diameter (0.357 μm). The water contact angle measures the hydrophilicity of silk film where at 15 kV and 3 ml/h has highest in hydrophilicity with contact angle 27.3o and 20.1o respectively. The Fourier Transform Infrared (FTIR) spectroscopy was used to characterize the raw cocoon, degummed silk, regenerated silk fibroin and silk/PVA solution. FTIR spectra showed that new characteristic peak of Amide III at 1445 to 1458 cm-1 presence in degummed silk, regenerated silk fibroin and silk/PVA solution. The result indicate that β sheet was formed after degumming process. The result also indicated that all peaks at silk/PVA solution have become stronger with addition of PVA content due to chemical bonding of silk and PVA. The silk/PVA based scaffold produced by dialysis free technique in this study can be promising candidate as biomaterial for various tissue engineering application.